Batch and Flow-Injection Spectrophotometric Determination of Thymol Using Procaine Hydrochloride as a New Chromogenic Reagent (Baghdad Science Journal, 2012)
New, simple and sensitive batch and Flow-injecton spectrophotometric methods for the determination of Thymol in pure form and in mouth wash preparations have been proposed in this study. These methods were based on a diazotization and coupling reaction between Thymol and diazotized procaine HCl in alkaline medium to form an intense orange-red water-soluble dye that is stable and has a maximum absorption at 474 nm. A graphs of absorbance versus concentration show that Beer’s law is obeyed over the concentration range of 0.4-4.8 and 4-80 µg.ml-1 of Thymol, with detection limits of 0.072 and 1.807 µg.ml-1 of Thymol for batch and FIA methods respectively. The FIA procedure sample throughput was 80 h-1. All different chemical and physical experimental parameters that affecting on the development and stability of the colored product were carefully studied and the proposed methods were successfully applied to the determination of Thymol in mouth wash preparations.